Anti-biofilm Properties of the Fecal Probiotic Lactobacilli Against Vibrio spp. - Kaur, Sumanpreet; Sharma, Preeti; Kalia, Namarta; Singh, Jatinder; Kaur, Sukhraj (Frontiers in Cellular and Infection Microbiology, 2018)
Diarrheal disease caused by Vibrio cholerae is endemic in developing countries including India and is associated with high rate of mortality especially in children. V. cholerae is known to form biofilms on the gut epithelium, and the biofilms once formed are resistant to the action of antibiotics. Therefore agents that prevent the biofilm formation and disperse the preformed biofilms are associated with therapeutic benefits. The use of antibiotics for the treatment of cholera is associated with side effects such as gut dysbiosis due to depletion of gut microflora, and the increasing problem of antibiotic resistance. Thus search for safe alternative therapeutic agents is warranted. Herein, we screened the lactobacilli spp. isolated from the fecal samples of healthy children for their abilities to prevent biofilm formation and to disperse the preformed biofilms of V. cholerae and V. parahaemolyticus by using an in vitro assay. The results showed that the culture supernatant (CS) of all the seven isolates of Lactobacillus spp. used in the study inhibited the biofilm formation of V. cholerae by more than 90%. Neutralization of pH of CS completely abrogated their antimicrobial activities against V. cholera, but had negligible effects on their biofilm inhibitory potential. Further, CS of all the lactobacilli isolates caused the dispersion of preformed V. cholerae biofilms in the range 62–85%; however, pH neutralization of CS reduced the biofilm dispersal potential of the 4 out of 7 isolates by 19–57%. Furthermore, the studies showed that CS of none of the lactobacilii isolates had antimicrobial activity against V. parahaemolyticus, but 5 out of 7 isolates inhibited the formation of its biofilm in the range 62–82%. However, none of the CS dispersed the preformed biofilms of V. parahaemolyticus. The ability of CS to inhibit the adherence of Vibrio spp. to the epithelial cell line was also determined. Thus, we conclude that the biofilm dispersive action of CS of lactobacilli is strain-specific and pH-dependent. As Vibrio is known to form biofilms in the intestinal niche having physiological pH in the range 6–7, the probiotic strains that have dispersive action at high pH may have better therapeutic potential.